HPLC Quantification of Cytotoxic Compounds from Aspergillus niger. (30th April 2017) - Uchoa, Paula Karina S.; de Lima, Leandro Bezerra; Pimenta, Antonia T. A.; de Oliveira, Maria da Conceição F.; Mafezoli, Jair; Lima, Mary Anne S.
Abstract : A high-performance liquid chromatography method was developed and validated for the quantification of the cytotoxic compounds produced by a marine strain of Aspergillus niger . The fungus was grown in malt peptone dextrose (MPD), potato dextrose yeast (PDY), and mannitol peptone yeast (MnPY) media during 7, 14, 21, and 28 days, and the natural products were identified by standard compounds. The validation parameters obtained were selectivity, linearity (coefficient of correlation > 0.99), precision (relative standard deviation below 5%), and accuracy (recovery > 96).